Investigating the causes of birth defects. - Sumbul Fatima; Shar , Nisar Ahmed (International Journal of Endorsing Health Science Research, 2023)
Background: Understanding and investigating the causes of birth defects is a critical approach toward the findings and development of helpful treatments and diagnostic strategies to overcome the issue of birth defects. We aim to investigate birth defects' causes by identifying the most common abnormal genes found in an inheritance pattern. Collecting genetic causes of the most common birth defects found in Pakistan and searching the link between birth defects and other harmful diseases. Methodology: The birth defects data is systematically gathered and critically analyzed to assess the role of insertions and deletions as the causative agents. Analysis was conducted on genomic data to investigate the genetic causes of congenital abnormalities. Results: The most common birth defects, namely neural tube defect (spina bifida), Facial palate (cleft/lip palate), heart defects (atrial septal defect, ventricular septal defect, tetralogy of Fallot), deletion syndrome, and laryngomalacia caused by the main problematic genes namely MTHFR, MEIS2, TBX1, and NKX2-5. The results show that about eighty-six percent (86%) of gene variants overlap completely with the defective genes transcript, including both insertions/gain and deletions/loss. Conclusion: Identification of the main genes which are involved in most of the common birth defects highlights the major twelve genes, namely LMNA, MTHFR, POMC, TTN, SLC25A13, FGFR3, GCH1, TBX1, MEIS2, NKX2-5, GATA4, and GATA6.